2018
DOI: 10.1021/acs.organomet.8b00494
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Non-Alkyl Functionalized Bis-Arene Complexes of Rhenium and 99(m)Technetium

Abstract: The synthesis of technetium and rhenium bis-arene sandwich complexes, [M­(η6-C6H6)2]+, requires AlCl3 according to Fischer–Hafner conditions. Its high reactivity limits syntheses to alkylated aromatic hydrocarbons but is generally incompatible with aromatic hydrocarbons, bearing heteroatoms in their side chains “R”. In a nuclear medical context, a synthesis to complexes of the [M­(η6-C6H5-R)2]+ type directly from [ReO4]− or [99mTcO4]− is desirable because postsynthetic derivatizations are not possible for 99mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
(53 reference statements)
3
20
0
Order By: Relevance
“…The irreversible nature of the two oxidation processes in 3a + suggests a ligand-and a metal-based oxidation, as observed for other sandwich complexes with functionalities bound to the arene rings. 5,7 In 3b + with two electron-withdrawing groups on the arenes, the metal-based oxidation is probably beyond the solvent window and only the oxidation of the aldehydes occurs. Meola et al reported the mixed-ring complex [Re(η 6 -C 6 H 6 )(η 5 -C 5 H 4 COH)] which also comprises an aldehyde.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 4 more Smart Citations
“…The irreversible nature of the two oxidation processes in 3a + suggests a ligand-and a metal-based oxidation, as observed for other sandwich complexes with functionalities bound to the arene rings. 5,7 In 3b + with two electron-withdrawing groups on the arenes, the metal-based oxidation is probably beyond the solvent window and only the oxidation of the aldehydes occurs. Meola et al reported the mixed-ring complex [Re(η 6 -C 6 H 6 )(η 5 -C 5 H 4 COH)] which also comprises an aldehyde.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The symmetry of all NMR spectra and therefore the free rotation around the rhenium axis is found for all [Re(arene) 2 ] + synthesized by our group so far. [5][6][7]16,17,27 Pyridines are prototypical ligands in many catalytic processes, e.g. for proton reduction in photocatalysis.…”
Section: Conjugation Of Ligands To Complexes 2a + -3b +mentioning
confidence: 99%
See 3 more Smart Citations